2014
DOI: 10.1126/science.1250691
|View full text |Cite
|
Sign up to set email alerts
|

Stop codon reassignments in the wild

Abstract: The canonical genetic code is assumed to be deeply conserved across all domains of life with very few exceptions. By scanning 5.6 trillion base pairs of metagenomic data for stop codon reassignment events, we detected recoding in a substantial fraction of the >1700 environmental samples examined. We observed extensive opal and amber stop codon reassignments in bacteriophages and of opal in bacteria. Our data indicate that bacteriophages can infect hosts with a different genetic code and demonstrate phage-host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(147 citation statements)
references
References 51 publications
6
131
0
1
Order By: Relevance
“…Microbiome (47) and environmental microbial sequencing (48) work is revealing organisms with new genetic code variations. At the same time, advances in synthetic biology are leading to new engineered genetic codes (3).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome (47) and environmental microbial sequencing (48) work is revealing organisms with new genetic code variations. At the same time, advances in synthetic biology are leading to new engineered genetic codes (3).…”
Section: Discussionmentioning
confidence: 99%
“…Although she is reluctant to comment on the likelihood of completely alien Earthlings, her research has shown that our DNA-based life is more diverse than previously thought (9). She found two new phyla of bacteria that use a different dialect in their genetic codes.…”
Section: Aliens On Earthmentioning
confidence: 97%
“…Although some organisms and mitochondria use non-canonical genetic codes, they typically involve a small number of codon reassignments in response to strong selective pressures [1]. For example, mitochondria are under selection to minimize genome size [1,2] and G+C content [3], while bacteria may use codon reassignment to evade viruses or to restrict horizontal gene transfer [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…While it is possible that more divergent genetic codes have yet to be discovered [5], several factors help to conserve the genetic code. Evolution tends to increase biological complexity [6], leading to the large genomes of modern free-living organisms (the smallest known genome with a full complement of essential genes has 580,070 base pairs encoding 470 predicted open reading frames [7]).…”
Section: Introductionmentioning
confidence: 99%